Implementation Of The Jogo Tonggo Program In Karangnangka Village, Kedungbanteng, Kabupaten Banyumas - Kusumaningsih, Oti; Saputra, Anggara Setya; Sutikno, Chamid; Mujib, Mujib (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2022)
ABSTRACT Important instruments in policy implementation are institutions and structures to achieve goals effectively and efficiently as expected. WHO declared COVID-19 as a pandemic until September 6, 2020. There were 26,468,031 cases of COVID-19 and 871,166 deaths worldwide. The Central Java Provincial Government has issued Instruction Number 1 of 2020 concerning Community Empowerment in Accelerating the Handling of COVID-19 at the Level of Community Units (RW) through the Establishment of the Jogo Tonggo Task Force. This research uses a qualitative method with a descriptive approach through the collection of words and pictures. The research design was carried out using a case study approach where the researcher developed a description and in-depth analysis of program implementation. Implementing the Jogo Tonggo program in Karangnangka Village, Kedungbanteng District, Banyumas Regency has been going well and effectively. This paper studied the aspect of an ideal policy per the rules and regulations of the central government, which is supported by policies at the local government level so that the program can realize properly. Target groups for affected communities by involving collaboration. The elements of the village government, village institutions, and the participation of the community. Implementing organizations comprise village government, village health, Dasa Wisma, village institutions, and communities. Environmental support maintains a culture of cooperation, both socially and economically. Keywords: Implementation, Jogo Tonggo, Collaboration, Institutions   ABSTRAK Instrumen yang penting dalam implementasi kebijakan adalah kelembagaan dan struktur untuk mencapai tujuan secara efektif dan efisien sesuai dengan yang diharapkan. WHO mengumumkan COVID-19 sebagai pandemi hingga tanggal 6 September 2020 tercatat jumlah kasus COVID-19 sebanyak 26.468.031 dan kasus meninggal sebanyak 871.166 di seluruh dunia. Pemerintah Daerah Provinsi Jawa Tengah telah mengeluarkan Instruksi Nomor 1 Tahun 2020 tentang Pemberdayaan Masyarakat Dalam Percepatan Penanganan COVID-19 di Tingkat Rukun Warga (RW) Melalui Pembentukan Satgas Jogo Tonggo. Metode penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif melalui pengumpulan berupa kata-kata dan gambar. Desain penelitian yang dilakukan dengan menggunakan pendekatan studi kasus dimana peneliti mengembangkan deskripsi dan analisis mendalam tentang implementasi program. Implementasi Progam Jogo Tonggo di Desa Karangnangka Kecamatan Kedungbanteng Kabupaten Banyumas sudah berjalan dengan baik dan efektif. Hal ini dikaji melalui aspek kebijakan yang ideal sesuai dengan aturan dan regulasi dari pemerintah pusat yang didukung dengan kebijakan pada level pemerintah daerah sehingga jalannya program dalam terrealisasi dengan baik. Kelompok sasaran kepada masyarakat terdampak dengan melibatkan kolaborasi unsur pemerintah desa, kelembagaan desa serta peran serta dari masyarakat. Organisasi pelaksana yang terdiri Pemerintah Desa, kesehatan desa, Dasa Wisma, kelembagaan desa dan masyarakat. Dukungan lingkungan yang mempertahankan budaya gotong royong baik sosial maupun ekonomi warga.   Kata Kunci: Implementasi, Jogo Tonggo, Kolaborasi, Kelembagaan